Problems in the Implication of the Word Strategy and Its Application in Translating Poetry: A Contrastive Linguistic Study - SEKHRI, Ouided (Journal of Human Sciences, 2015)
There is some disagreement about translation strategies in general and the strategies used in translating poetry in particular amongst translation scholars not only in the terminology but also in the concept since different labels such as technique, procedure, method, and strategy are utilized. These terms can generally overlap which confuses some concepts with the others. In this respect, this study focuses on translation strategies which are the ways that a translator may follow when finding exact equivalents is almost impossible. These strategies swing between domesticating the source text to the norms that govern the target text and foreignizing the target text to the rules that manage the source text. Thus, distinguishing between main and secondary ideas, establishing conceptual relationships, searching for information, paraphrasing, back translating, translating out loud, establishing an order for documentation, etc. help the translator find a solution in order to mediate between the source text and the target text. For that, since there is no unified model about the strategies used in translating poetry; we shall try to find a solution through analyzing five poems of Robert Frost using the method of analyzing literary texts.